(untitled) (Marketing Journal, 2025)
This article covers the possibilities of introducing digital technologies in the fashion industry. Scientific and practical proposals for the application of modern technologies such as artificial intelligence, blockchain technologies, Augmented Reality (AR) and Internet of Things (IoT) in the fashion industry have been given.